Molecular mapping of QTLs for grain dimension traits in Basmati rice - Malik, Ankit; Kumar, Aruna; Ellur, Ranjith Kumar; Krishnan S, Gopala; Dixit, Deepshikha; Bollinedi, Haritha; Vinod, KK; Nagarajan, M; Bhowmick, PK; Singh, NK; Singh, AK (Frontiers in Genetics, 2022)
Basmati rice is known for extra-long slender grains, exceptional kernel dimensions after cooking, high volume expansion and strong aroma. Developing high yielding Basmati rice varieties with good cooking quality is a gigantic task. Therefore, identifying the genomic regions governing the grain and cooked kernel dimension traits is of utmost importance for its use in marker assisted breeding. Although several QTLs governing grain dimension traits have been reported, limited attempts have been made to map QTLs for grain and cooked kernel dimension traits of Basmati rice. In the current study, a population of recombinant inbred lines (RIL) was generated from a cross of Sonasal and Pusa Basmati 1121 (PB1121). In the RIL population, there was significant positive correlation among the length (RRL: rough rice length, MRL: milled rice length, CKL: cooked kernel length) and breadth (RRB: rough rice breadth, MRB: milled rice breadth and CKB: cooked kernel breadth) related traits, while there was significant negative correlation between them. QTL mapping has led to identification of four major genomic regions governing MRL and CKL. Two QTLs colocalize with the earlier reported major gene GS3 and a QTL qGRL7.1, while the remaining two QTLs viz., qCKL3.2 (qMRL3.2) and qCKL4.1 (qMRL4.1) were novel. The QTL qCKL3.2 has been bracketed to a genomic region of 0.78Mb between the markers RM15247 and RM15281. Annotation of this region identified 18 gene models, of which the genes predicted to encode pentatricopeptides and brassinosteroid insensitive 1-associated receptor kinase 1 precursor may be the putative candidate genes. Further, we identified a novel QTL qKER2.1 governing kernel elongation ratio (KER) in Basmati rice.